Difficulties in the management of an Askin tumor in a pediatric patient with cystic fibrosis: case report and literature review - Marinău, Cristian; Csep, Andrei; Sava, Cristian; Iuhas, Alin; Niulaș, Larisa; Szilagyi, Ariana; Ritli, Ladislau; Balmoș, Andreea; Jurca, Claudia (Frontiers in Pediatrics, 2023)
Treating Ewing's Sarcoma of the thorax (Askin's tumor) with antineoplastic therapy in a malnourished cystic fibrosis patient colonized with Pseudomonas aeruginosa and Staphylococcus aureus may carry a significant potential for complications. We present the case of a known cystic fibrosis patient, diagnosed with Askin's tumor 5 years ago. Despite facing severe neutropenia, exacerbations of cystic fibrosis with Pseudomonas aeruginosa infections, and challenges in maintaining adequate caloric intake during the oncological treatment, the patient's outcome has been favorable. Chemotherapy doses had to be adjusted, and continuous antibiotic treatment was introduced throughout the course of therapy to reduce the frequency and intensity of exacerbations. Approximately 5 years after the cancer diagnosis, with no signs of relapse, the patient was started on CFTR (Cystic fibrosis transmembrane conductance regulator) modulator treatment. This intervention has successfully corrected the weight deficit. The coincidence of Ewing's sarcoma of the chest wall and cystic fibrosis in a single patient is 2.857x10 -5 % and to the best of our knowledge, this scenario has not been documented before.